Social Media Considerations in Higher Education: Recommendations for Radiologic Sciences Education. - Watts, Lynette K. (Radiologic Science & Education, 2018)
Social media has been incorporated as a learning tool into the higher education system, with health sciences and human services programs developing ways of implementing its use in the curricula. Before incorporating social media into privacy-driven fields, benefits and barriers should be examined carefully. Current research presents more use of social media among medical, nursing, and allied health fields than in radiologic sciences. The purpose of this literature review is to present barriers, benefits, and recommendations for social media use in radiologic sciences and to determine if medical imaging programs are using social media to enhance learning in the curricula.